Dynamic simulation of 3D-printed foods - Shir Goldfinger; Hod Lipson; Jonathan Blutinger (Future Foods, 2024)
Simulation environments for 3D-printed structures are crucial to assess failure modes prior to printing. Multi-ingredient additive manufacturing (AM) of food is particularly susceptible to failure due to differences in ingredient viscoelasticity. Current simulation software handles objects in their final fabricated form. Here, we present a simulation framework that digitally replicates the deposition process of disparate material pastes using a physics-based simulator. Our simulator takes a digital recipe file (G-code) as input and uses Bifrost—a plug-in for Autodesk Maya—to generate a digital replica of the 3D printing process. We ground truth our print simulator by successfully reproducing a custom designed seven-ingredient dessert. Designs that are dynamically simulated prior to being printed develops user intuition for stable structures, mitigates material waste, and enables faster proofing of printable designs to achieve structural and aesthetic creations.